Comparative Study of Postoperative Infection Rate between Ventriculoperitoneal Shunt and Lumboperitoneal Shunt in Patients with Hydrocephalus - Tangpongsirikul, Supapon (Thai Journal of Neurological Surgery, 2025)
This study aims to compare the infection rate of between ventriculoperitoneal shunt and lumboperitoneal shunt in hydrocephalus patients in Trang hospital. This is a retrospective comparative study in the patients with hydrocephalus who underwent ventriculoperitoneal or lumboperitoneal shunts in Trang hospital during 1 January 2019-31 December 2020. The inclusion criteria is that the patients must be over 15 years old. The demographic data were analyzed. The patients were followed-up for 6 months after surgery whether there would have any postoperative infection. The results show that there were 22 patients underwent ventriculoperitoneal shunt to treat various type of hydrocephalus. Half of the patients are male, the other half are female. The mean age was 54.05 (18-83). There were 4 patients (18.2%) having postoperative infection after VP shunt. There were 12 normal pressure hydrocephalus patients underwent lumboperitoneal shunt. Six patients are male, and the rest of the patients are female. The average age was 75.25 (63- 89). There was no postoperative infection after 6 months of follow-up. The p-value of difference between infection rate of each group below than 0.001, so there was greater infection rate in the group undergoing VP shunt significantly. The conclusion is that the postoperative infection rate after VP Shunt is greater than LP shunt and associated factor is timing of operation and causes of hydrocephalus.